The Restructuring of a Cross-border Group in German StaRUG Proceedings : Some Takeaways from Spark Networks SE - Madaus, Stephan (European Insolvency and Restructuring Journal, 2024)
Case note on AG Berlin Charlottenburg, 4.1.2024, NZI 2024, 193. This case note discusses the restructuring proceedings of Spark Networks SE under the German StaRUG. The plan aimed to financially reorganise the company, primarily its foreign law-governed debt and equity structure. The plan included an equity wipeout of existing shareholders, enabling one of the major creditors to assume control of the company through a debt-for-equity swap. Notably, the Spark Networks deliberately opted for a StaRUG proceeding over alternative options. This provided the Berlin restructuring court with an opportunity to address contentious legal issues stemming from the relatively new StaRUG legislation, particularly concerning company valuation and the fair distribution of the company’s value post-restructuring among plan stakeholders. Spark Networks’ StaRUG proceedings received recognition as a foreign main proceeding under 11 U.S.C. § 101(23), paving the way for recognition of the plan under the U.S. Chapter 15 proceedings. Spark Networks’ plan marks the first ever cross-border restructuring under the German StaRUG and U.S. Chapter 15.